2007
DOI: 10.1007/s10495-006-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic mutant p53 increases Bcl-2 expression in estrogen receptor-positive breast cancer cells

Abstract: The Bcl-2 gene is positively regulated by estrogen (E2) primarily through E2-response elements in the coding region and a putative p53 negative regulatory element (NRE) containing a short upstream open reading frame (uORF). The ability of mutant p53 to repress or induce Bcl-2 expression is controversial. In this study E2-receptor positive (ER(+))/wild-type p53 MCF-7cells were transfected with p53Delta291, which lacks a nuclear localization signal or a DNA binding domain mutant, p53(173L). Both p53 mutants but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…One pathway is the deathreceptor pathway and the other is the mitochondrial pathway (Chandra et al 2002;Teijido and Dejean 2010); the latter has been regarded as an important mediator of cell apoptosis in mammals (Zhang et al 2010). In the mitochondrial pathway, Bcl-2 family members carried the responsibility for the regulation of apoptosis in different situations, including the antiapoptotic Bcl-2 protein and pro-apoptotic Bax protein (Pratt et al 2007). In this study, we considered the Bax/Bcl-2 ratio a crucial factor in determining the fate of cells toward apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…One pathway is the deathreceptor pathway and the other is the mitochondrial pathway (Chandra et al 2002;Teijido and Dejean 2010); the latter has been regarded as an important mediator of cell apoptosis in mammals (Zhang et al 2010). In the mitochondrial pathway, Bcl-2 family members carried the responsibility for the regulation of apoptosis in different situations, including the antiapoptotic Bcl-2 protein and pro-apoptotic Bax protein (Pratt et al 2007). In this study, we considered the Bax/Bcl-2 ratio a crucial factor in determining the fate of cells toward apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Only wild-type p53 has been conclusively shown to trigger apoptosis; therefore, it is particularly important to consider that therapeutics targeted against the wild-type protein may be ineffective in cancer cells which contain mutant p53. For instance, one study has shown that in estrogen-positive breast cancer cells, expression of a truncated p53 lacking the C-terminal 102 amino acids increases BCL-2 expression by alleviating the repression by endogenous wild-type p53, thus decreasing apoptosis [129]. …”
Section: P53: a Master Regulator Of Autophagy And Apoptosismentioning
confidence: 99%
“…Positive association in breast cancer has been found between mutant p53 and expression of the anti-apoptotic splice variant of Survivin (92). Mutant p53s have been also found to increase the levels of Bcl-2 (93). Recently, Bcl-2 has been described to be frequently overproduced in triple-negative breast cancers (TNBCs) and, in contrast to other mammary tumor types, to correlate with poor patient survival (94).…”
Section: Mutant P53 Involvement In Mechanisms Of Breast Cancer Develomentioning
confidence: 99%